Formation of ecological consciousness of younger younger schoolchildren in conditions of sustainable development of society - Конельська, І. М.; Терлецька, Н. М. (Pedagogy of Higher and Secondary Education, 2012)
Konelska I. M., Terletska N. M. Formation of ecological consciousness of younger students in conditions of sustainable development of society. The article considers the basis for the development of ecological consciousness of students in the light of the objectives of education in the conditions of sustainable development of the society, the main principles of forming the ecological consciousness of younger schoolchildren.